<span>1.Rename with common denominators.
2.Regroup the first fraction.
3.Subtract the whole numbers and numerators.
<span>4.Simplify (if necessary)</span></span>
M5 minus M6 will get M1
So 62 - 38 = 24
24 x 3 = 72
So M3 is 72
So to start you will need to divide by -5 then -5 divided by -5 cancelle
I can’t see it there’s no picture lol
Answer:
third number = 4,
equation of y, y = 5x - 11
equation of n, n = 4x
equation of x, n + x + y =19
Step-by-step explanation:
so lets write evertything as a n equation. n + x + y =19. N is the first number, x is the second number, and y is the third number. We will write the equation for y as follows 5x - 11. N will be four times the second number, so 4x. If substitute the values for out equation for x we will find what x equals to. So (4x) + x + (5x - 11) = 19
10x = 30
x = 3.
Then you substiute the answer for x in the equation for y. This will get you 5(3) - 11
15 - 11
4 = third number